2019
DOI: 10.3390/su11184956
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Value and Customer Adoption of Electric and Hybrid Vehicles

Abstract: Internal combustion engine vehicles are a key source contributing to urban air pollution. In order to reduce noxious emissions and reliance on fossil fuels, governments and the automobile industry have started promoting the adoption of electro mobility (EM) options over the last few years, albeit with limited success in terms of market penetration. This study aimed to improve the current understanding of factors influencing customers’ intentions to adopt EM options. Building on the theories of perceived value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…In a study of a comparable sector, green luxury cars, results similarly showed that social influence, showing as status motivation, is an important factor of purchasing intention [52]. Similar findings were also produced by Higueras-Castillo, Molinillo, Coca-Stefaniak & Liebana-Cabanillas [53] whose research pointed out that car performance greatly impacts purchasing intention for electric vehicles, but they did not confirm our findings about the impact of social influence. However, these comparisons with similar research cannot be directly compared to our research since the main aspect of autonomous cars lies in its self-driving ability and not in its luxury or propulsion.…”
Section: Discussionsupporting
confidence: 46%
“…In a study of a comparable sector, green luxury cars, results similarly showed that social influence, showing as status motivation, is an important factor of purchasing intention [52]. Similar findings were also produced by Higueras-Castillo, Molinillo, Coca-Stefaniak & Liebana-Cabanillas [53] whose research pointed out that car performance greatly impacts purchasing intention for electric vehicles, but they did not confirm our findings about the impact of social influence. However, these comparisons with similar research cannot be directly compared to our research since the main aspect of autonomous cars lies in its self-driving ability and not in its luxury or propulsion.…”
Section: Discussionsupporting
confidence: 46%
“…An application of electrical power as an alternative power source for vehicles allows for the development of the sustainable mobility concept. This concept aims at reducing the number of combustion engine vehicles, particularly in urban areas, and thus reducing their negative influence on the environment and human health [74].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this, several studies have found that price is a barrier to many potential adopters [25,73,74]. Similarly, perceived value for money has also been found to have a significant positive effect on consumers' attitude towards EVs [20], whilst earlier research has shown that financial incentives [31] or a significant reduction in market prices would encourage the adoption of these vehicles by potential consumers [75][76][77]. Moreover, Tran et al [78] found that the most influential factor among early adopters of EVs is the financial benefit.…”
Section: The Role Of Financial and Technical Attributes In The Adoptimentioning
confidence: 96%
“…Common examples of the first category include age, gender, income, education level [16,17], social influence, environmental concern, and innovativeness [18,19]. Attributes used in earlier research studies to analyse consumer behaviour related to the adoption of EVs include price [20], driving range [21], availability of charging points [22] and vehicle acceleration [23].…”
Section: Introductionmentioning
confidence: 99%